Sustainable livelihoods and indicators for regional development in mining economies. Issue 2 (April 2015) - Horsley, Julia; Prout, Sarah; Tonts, Matthew; Ali, Saleem H.
Highlights Robust indicators are needed to understand the relationship between mining and development. To date, there has not been a consistent evidence-based approach to selecting relevant indicators. The sustainable livelihoods (SL) framework provides a sound basis for indicator selection. The five capitals for sustaining livelihoods are the central focus of spatio-temporal measurement. Adaptable to multiple scales, SL considers stakeholder perspectives in indicator selection.